Light People: Professor Dayong Jin - Ying Zhang (Nature Publishing Group, 2021)
Editorial He pioneered a new family of nanoscopic probes that can up-convert infrared photons into intense visible light, and won the Australian Museum Eureka Prize for Interdisciplinary Scientific Research in 2015. He created new kinds of microscopes that allow us to watch molecules at work inside living cells, and won the Australian Prime Minister’s Prize for Science Malcolm McIntosh Prize for Physical Scientist of the Year 2017. The Australian newspaper identified him among 100 “rock stars of Australia’s new economy” as the Knowledge Nation 100. This year, at his age of 42, he won the Australian Laureate Fellowship and was elected to the fellowship of Australian Academy of Technology and Engineering. This is Dayong Jin, a Distinguished Professor at the University of Technology Sydney and a Chair Professor at Southern University of Science and Technology, as well as the editorial manager in Sydney office and the perspective column editor of Light: Science & Applications (LSA). Light People is a featured column of high-end interviews with outstanding scientists. On this issue, it is our great honor to invite Professor Dayong Jin to provide his perspectives on his work, end-user driven research, student mentoring and team building philosophy. In the following, let’s take a closer look at the research life of Professor Dayong Jin, and appreciate his style and the story behind his success.